Freedom or Restraint: Redefining the Concept of Human Security within the Indonesian Muslim Community - Erwin Nur Rif'ah (Jember University Press, 2017)
This study aimed to explore the changing concept of human security in Indonesia. It concentrates on how Indonesian Muslim define human security based on their experiences and opinion by referring to the definition of Human security provided by the Commission of Human Security. The setting of this study is in two districts: Cianjur, West Java and Bulukumba, South Sulawesi where the Perda Sharia has been implemented. The research focuses on the interplay between human security and women’s security discourse and the changing religious, social and political constellation in relation to the implementation of Perda Sharia (Sharia-influenced Regional Regulation). Human security, by reffering to the concept of Commission of Human Security’s (CHS), means: protecting fundamental freedoms; ‘freedom from want, freedom from fear, and freedom to take action on one’s own behalf’. This study found that, although the implementation of Perda Sharia has been widespread and its impact on the security of women has been subject to many discussion, however, the discussion on the concept of human security and women’s security has been subject to little discussion and is not popular in Indonesia. Surprisingly, that most informants argued that freedom is a western concept, which has negative connotations and is contrary to Islamic teachings and Indonesian culture. And, the informants argued that they did not seek ‘freedom’, but rather sought ‘refrain’